#### Answer

y=1

#### Work Step by Step

Simplifying
17 + -4y = 14 + -1y
Solving
17 + -4y = 14 + -1y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add 'y' to each side of the equation.
17 + -4y + y = 14 + -1y + y
Combine like terms: -4y + y = -3y
17 + -3y = 14 + -1y + y
Combine like terms: -1y + y = 0
17 + -3y = 14 + 0
17 + -3y = 14
Add '-17' to each side of the equation.
17 + -17 + -3y = 14 + -17
Combine like terms: 17 + -17 = 0
0 + -3y = 14 + -17
-3y = 14 + -17
Combine like terms: 14 + -17 = -3
-3y = -3
Divide each side by '-3'.
y = 1
Simplifying
y = 1